Teachers' Perception of Principal's Communication in the Management of Educational Units: A Case Study of Schools in the Coastal Area of Lhokseumawe City - Ali, Muhammad; Mursalin, M; Armita, Desi (Management Research and Behavior Journal, 2024)
This study examines teachers' perception of school principals' communication in the management of educational units in schools in coastal areas of Lhokseumawe City. The background is the importance of effective communication to create a conducive work environment and support learning in coastal areas that have unique challenges. The research method used is qualitative descriptive with data collection techniques through questionnaires, interviews, and observations. The results of the study show that the majority of teachers have a positive perception of the principal's communication. Principals who are skilled in communication are able to direct, motivate, and provide constructive feedback, which improves teacher performance and job satisfaction. These findings support the organizational communication theory by Robbins and Judge (2013) and the transformational leadership theory by Bass and Avolio (1994). The study also found communication challenges related to differences in styles and expectations, but principals who communicate openly and transparently are more effective at overcoming these challenges. The implication is that it is important to develop a communication training program for school principals to improve the quality of education in coastal areas.